2000
DOI: 10.1016/s1074-7613(00)80162-4
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of Signaling Cascades through gp130 In Vivo

Abstract: We generated a series of knockin mouse lines, in which the cytokine receptor gp130-dependent STAT3 and/or SHP2 signals were disrupted, by replacing the mouse gp130 gene with human gp130 mutant cDNAs. The SHP2 signal-deficient mice (gp130F759/F759 were born normal but displayed splenomegaly and lymphadenopathy and an enhanced acute phase reaction. In contrast, the STAT3 signal-deficient mice (gp130FXQ/FXXQ) died perinatally, like the gp130-deficient mice (gp130D/D). The gp130F759/F759 mice showed prolonged gp13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
84
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(94 citation statements)
references
References 44 publications
10
84
0
Order By: Relevance
“…By day 4, the overall levels of activated MAPK were reduced, and LIF treatment did not increase MAPK phosphorylation, whereas EGF was able to stimulate MAPK on all days. This result suggests that an increase in levels of MAPK by LIF are not essential in inducing a receptive state in the LE, consistent with the observation that mutated derivatives of gp130, which do not activate MAPK, have no effect on fertility (30). The reduced levels of MAPK at the time of uterine receptivity are particularly intriguing, as other studies have revealed cross-talk between the Jak-Stat and MAPK pathways.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…By day 4, the overall levels of activated MAPK were reduced, and LIF treatment did not increase MAPK phosphorylation, whereas EGF was able to stimulate MAPK on all days. This result suggests that an increase in levels of MAPK by LIF are not essential in inducing a receptive state in the LE, consistent with the observation that mutated derivatives of gp130, which do not activate MAPK, have no effect on fertility (30). The reduced levels of MAPK at the time of uterine receptivity are particularly intriguing, as other studies have revealed cross-talk between the Jak-Stat and MAPK pathways.…”
Section: Discussionsupporting
confidence: 86%
“…The MAPK pathway also is activated by LIF in a variety of cell types and has an important effect in modulating Stat3 activity (28)(29)(30). Purified LE from days 3-5 was treated with either EGF or LIF to assay MAPK phosphorylation.…”
Section: Lif Target Tissues In the Uterusmentioning
confidence: 99%
“…Response to GM-CSF-Previous studies have shown that ablation of Shp2 enhances Stat3 activation (33)(34)(35). To test whether Shp2 negatively regulates Stat3 activation in hematopoietic progenitors, we retrovirally transduced low density mononuclear cells with empty vector (MIEG3), WT Shp2, or Shp2E76K, one of the most common activating PTPN11 mutations observed in JMML (9, 10, 13, 36), sorted for transduced enhanced green fluorescent protein (EGFP)-expressing cells, and cultured into macrophage progenitors as previously described (27) Fig.…”
Section: Mutant Shp2 Negatively Regulates Stat3 Activation Inmentioning
confidence: 99%
“…The IL6/gp130/STAT3 (interleukin-6/glycoprotein 130/signal transducer and activation of transcription 3) pathway has been shown to play a role in the development of gastric cancer (24,25). IL6 exerts its biological activities through the receptor subunit gp130 (26).…”
mentioning
confidence: 99%
“…However, disrupting this balance in the gp130 "knock-in" mouse induced premalignant lesions, including atrophy, intestinal metaplasia, dysplasia, and ultimately gastric cancer (24). Similarly, when the IL6 cytokine family signaling pathway is disrupted, increased STAT3 signaling may favor development of gastric adenomas, whereas increased SHP2/ERK 2 signaling may lead to mucosal inflammation (25,30).…”
mentioning
confidence: 99%